Qualitative and quantitative analysis of self-reported sensory issues in individuals with neurodevelopmental disorders - Wada, Makoto; Hayashi, Katsuya; Seino, Kai; Ishii, Naomi; Nawa, Taemi; Nishimaki, Kengo (Frontiers in Psychiatry, 2023)
Individuals with neurodevelopmental disorders, such as autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), and specific learning disorders (SLD) have various types of sensory characteristics. This study investigated sensory issues in individuals with neurodevelopmental disorders using a web-based questionnaire for qualitative and quantitative analysis, categorized the contents of their three most distressful sensory issues, and evaluated their order of priority. Auditory problems were reported as the most distressing sensory issue among the participants. In addition to auditory problems, individuals with ASD frequently reported more tactile problems, and individuals with SLD reported more visual problems. Among the individual sensory issues, in addition to aversion to sudden, strong, or specific stimuli, some participants reported confusions regarding multiple stimuli presenting concurrently. Additionally, the sensory issue related to foods (i.e., taste) was relatively more common in the minor group. These results suggest that the diversity of sensory issues experienced should be carefully considered when aiding persons with neurodevelopmental disorders.